The impact of COVID-19 on coordinated specialty care (CSC) for people with first episode psychosis (FEP): Preliminary observations, and recommendations, from the United States, Israel and China. Issue 3 (2nd October 2021) - Meyer-Kalos, Piper S.; Roe, David; Gingerich, Susan; Hardy, Kate; Bello, Iruma; Hrouda, Debra; Shapiro, Daniel; Hayden-Lewis, Katherine; Cao, Liping; Hao, Xiaoyu; Liang, Yanbin; Zhong, Siqian; et al.
ABSTRACT: In the wake of COVID-19, mental health providers and treatment programs are adapting rapidly to the challenges in engaging people and delivering treatment with limited guidance. This paper will explore the challenges associated with delivering treatment within coordinated specialty care (CSC) programs for people with first episode psychosis. Suggestions for treatment will take into consideration experiences with stress, changes to the pursuit of work and school, and increased time spent with families. Drawing on the experience of several CSC programs in the United States, Israel, and China, we describe the impact and modifications to the core treatment elements in CSC including medication, family interactions, supported employment and education, individual therapy, peer support and the way they are delivered. The paper includes recommendations based on experiences from CSC programs to help staff members, participants, and family members better identify, prepare, cope and respond to the unique new challenges and suggests modifications that can be made during various stages of the coronavirus pandemic.